Usability and accessibility of urban service areas with increasing epidemics: the case of Bursa/Turkey: The effect of urban service areas on the quality of life in the post-pandemic period - Ender Altay, Elvan; Şenay, Diba (TeMA - Journal of Land Use, Mobility and Environment, 2023)
The concept of urban life quality, which comes to the fore with urbanization and evaluates the effects of environmental variables on the well-being of the citizens in every respect, is directly related to the quality, quantity, and sufficiency of the urban service areas of the cities. In this study, cultural spaces, open spaces, and green areas in the central district of Bursa are classified as 12 types of urban service areas were examined. Within the framework of the method setup, the existence and distribution of urban services were evaluated within the scope of pre- and post-pandemic conditions, and solution suggestions were developed to increase the quality of life. In this context, it was determined that 47 out of 136 neighborhoods did not have urban service areas, and per capita values were found to be sufficient in only 10 neighborhoods. It is seen that these 10 neighborhoods have more recreational activity opportunities compared to other neighborhoods. The systematic method in the study was created in order to evaluate it as a plan base for physical planning studies in the study area and to shed light on the development of suggestions for increasing the quality of life for each city in general.